2015
DOI: 10.1136/bcr-2014-209055
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured splenic abscess causing pneumoperitoneum: a rare cause revisited

Abstract: SUMMARYWe present a case report of splenic abscess causing pneumoperitoneum in a case of uncontrolled diabetes. The patient presented with chronic pain abdomen and fever which later evolved to acute abdomen during the course of hospital stay. An X-ray showed pneumoperitoneum and exploratory laparotomy was performed under a strong clinical suspicion of hollow viscus perforation. The patient was treated with antibiotics and had an uneventful recovery. BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 5 publications
1
12
0
2
Order By: Relevance
“…The most common organisms isolated on bacteriological culture is case of splenic abscess are Gram-negative bacilli ( K. pneumoniae , Escherichia coli ) and Gram-positive cocci ( Staphylococcus aureus ), although a vast variety of microorganism have been described 10 11. Due to presence of gas-producing organisms in the splenic abscess, may cause pneumoperitoneum after burst into the abdomen 11 12. We also noted presence of gas-producing organism as a cause of pneumoperitoneum in our case.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The most common organisms isolated on bacteriological culture is case of splenic abscess are Gram-negative bacilli ( K. pneumoniae , Escherichia coli ) and Gram-positive cocci ( Staphylococcus aureus ), although a vast variety of microorganism have been described 10 11. Due to presence of gas-producing organisms in the splenic abscess, may cause pneumoperitoneum after burst into the abdomen 11 12. We also noted presence of gas-producing organism as a cause of pneumoperitoneum in our case.…”
Section: Discussionsupporting
confidence: 53%
“…In general, failure to respond to antibiotics with or without percutaneous drainage necessitates the splenectomy. Splenectomy is the final definitive management for ruptured, severely damaged spleen or in cases not responding to percutaneous drainage 5 12…”
Section: Discussionmentioning
confidence: 99%
“…8 It may be due to hematogenous spread to a normal or abnormal spleen and also due to extension of abscess from adjacent organs like pancreas, diverticular abscess or subphrenic abscess. 11 The most commonly isolated organisms include gram negative bacteria (E. coli, Klebsiella), gram positive bacteria (streptococcus, staphylococcus), mycobacterium, fungi and parasites. 9 The non-specific presentation of splenic abscess makes it difficult to diagnose clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Leukocytosis is present in most patients (78%). When an abscess is ruptured, acute abdomen and generalized peritonitis ensues, when intraabdominal free air may develop [ 5 ]. Culhaci et al [ 6 ] reported that they operated all patients with splenic abscess due to clinical signs and symptoms of acute abdomen, and discovered splenic abscess rupture in two of them.…”
Section: Discussionmentioning
confidence: 99%